Development and growth of auricular cartilage and muscles: A study using human fetuses. (June 2020) - Honkura, Yohei; Hayashi, Shogo; Kim, Ji Hyun; Murakami, Gen; Abe, Hiroshi; Rodríguez-Vázquez, José Francisco; Katori, Yukio
Abstract: Objectives: The auricle is a key target in pediatric plastic surgery and is considered to develop from a ring- or funnel-like arrangement of six hillocks in the embryo. However, there has been no report showing the morphologies of the auricular muscle and cartilage after midterm in humans. Methods: We examined histological sections of 20 near-term human fetuses (29–40 weeks) and those from 7 midterm fetuses (15–16 weeks). Results: At midterm, the auricular cartilage was a single wavy plate with the helicis major muscle (HMM). The superior and posterior auricular muscles (SAM, PAM) were inserted into the middle parts, and the anterior auricular muscle (AAM) was inserted into the lowest part of the cartilage plate, while the tragus and antitragus were not clearly identified. In near-term fetuses, the cartilage plate varied in size and shape between specimens. The scapha and antihelix were separated from the cartilage plate with major or minor involvement of the HMM from the initial mass along the helix. The SAM inserted to the crus helix or the developing scapha, while the insertion sites of the AAM and PAM into the helix were stable. The tragus–antitragus cartilages were well-developed and they sandwiched a deep notch of skin below the helix tail. The antitragicus muscle was more evident than the tragicus muscle. An unnamed muscle was evident along the external acoustic meatus. The other intrinsic muscles, including the transverse and oblique muscles, might develop from the HMM after birth. Conclusions: Development of the auricle was advanced after midterm. However, a single wavy plate-like cartilage was maintained until late-stage. Near term, the antihelix and scapha developed from the plate-like core of the auricle and the tragus and antitragus were added in the antero-inferior side of the cartilage plate. Establishment of muscle arrangements was markedly delayed compared to cartilage development. Altogether, the classical concept of an initial funnel-like arrangement of cartilage anlagen might have been biased by studies of adult morphology.